Tantangan Dan Strategi Pengembangan Subak Sebagai Daya Tarik Wisata Berkelanjutan di Desa Pandak Gede Kabupaten Tabanan - Wiwin, I Wayan; Indrawati, Ni Made Diah; Trisnadewi, Komang Irma; Lestari, I Gusti Ayu Dewi; Hawani, Ni Putu Isra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research aims to examine the potential development of subak as a rural tourism attraction in Pandak Gede Village, Tabanan Regency, as well as to identify the challenges and strategies needed to realize it. Subak, as a traditional irrigation system recognized by UNESCO as a World Cultural Heritage, holds significant historical, social, and ecological value. Through a qualitative approach and case study method, this research collects data from field observations, in-depth interviews, and document analysis. The research results show that the subak in Pandak Gede Village has great potential as a tourist attraction due to its unique culture and beautiful landscape. However, there are significant challenges in development, such as a lack of public awareness and limited infrastructure. This research suggests development strategies that involve community participation, strengthening cooperation with the government, and ongoing promotion to support the successful development of subak as a rural tourism attraction. The results of this research are expected to contribute to the development of sustainable tourism in Bali and the preservation of local culture. Keywords: Subak, Rural Tourism, Village Tourism Development, Sustainable Tourism.